Evolving knowledge bases : specification and semantics - Leite, João Alexandre (Frontiers in artificial intelligence and applications ;, 2003)
An Evolving Knowledge Base (EKB) is capable of self evolution by means of its internally specified behaviour. In this thesis the author incrementally specifies, semantically characterizes and illustrates with examples, the concepts and tools necessary to the development of EKBs.